Can a 1960s library be transformed for the 21st century? - Delcarmine, Nadine (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2004)
This paper describes the renovation of Grenoble University’s library. It is the main inter-university documentary cooperation service (SICD2) network in Grenoble, which serves two Universities: Stendhal and Pierre Mendès France. Administratively it is attached to the latter. After the 1989 Micquel Report, which was a severe appraisal of France’s university libraries, the state showed its intention to upgrade them by preparing the U2000 programme. The objectives were to create more working places, unrestricted access to documentation, improve user comfort, and change the image of the libraries. In June 1994, replying to representations by the President of Grenoble’s Université Pierre Mendès-France (UPMF) on safety problems at the Law and Humanities Library, the Construction and Maintenance Department at the Ministry of Education requested an "all-encompassing approach to upgrading work, covering safety and refurbishment to as-new standard", and stipulated that "this policy review should be conducted as part of the preparation of the new establishment contract". This context gave rise to the rehabilitation and restructuring of the library. In 1995, the universities and the SICD set themselves an ambition: to turn the 1960s library into a documentary resource for the 21st century, making it the lynchpin of the SICD library network and providing suitable premises. The project symbolically called "Doc2000" was created. After a long gestation period, during which funding was gradually secured, the project entered the execution phase. The relevance of the project was tested by numerous twists and turns: a fruitless invitation to tender and shifting project ownership; three university presidents; two SICD directors and one interim-director, who also directed the university library; and the involvement of two project leaders. I intend to show how hard it is for the library, at the end of the process chain, to reconcile and align the scheduling of the works, the scheduling of the service changes and structural organisation, and the works themselves. I’ll outline the basic economics of the project, which combines an obsolete building with thoughts on the necessary evolution of its services. Then, I’ll attempt to show how we tried to develop the existing building to cater for evolving services. Lastly, I’ll explain why execution of the works was like sailing down a long tempestuous river.